Answer:
F₁ =
F₀
Step-by-step explanation:
Newton's law of universal gravitation states that the force of attraction or repulsion, F, between two particles of masses M₁ and M₂ is directly proportional to the product of these particles and inversely proportional to the square of the distance, r, between the two particles. i.e
F ∝ M₁M₂ / r²
F = GM₁M₂ / r² --------------------(i)
Where;
G is the constant of proportionality.
From equation (i), since the force is inversely proportional to the square of the distance, holding other variables constant, the equation can be reduced to;
F = k / r²
This implies that;
Fr² = k -------------------(ii)
Now, according to the question;
F = F₀
Substitute this into equation (ii) as follows;
F₀ r² = k ----------------(iii)
Also, when the distance of separation, r, is trippled i.e r becomes 3r;
F = F₁
Substitute these values into equation (ii) as follows;
F₁(3r)² = k
9F₁r² = k ---------------(iv)
Substitute the value of k in equation (iii) into equation (iv) as follows;
9F₁r² = F₀ r² --------------(v)
Cancel r² on both sides of equation (v)
9F₁ = F₀
Now make F₁ subject of the formula
F₁ =
F₀
Therefore, the new force F₁ =
F₀